Briefpublizistik der Frühen Neuzeit: historische und systematische Überlegungen - Meierhofer, Christian; Spiekermann, Björn (Daphnis, 2022)
Abstract This introductory article examines early modern letter-writing in its ambiguous state between private and public communication by providing a few historical and systematic perspectives. From a historical point of view, it can be shown how several humanists tried to outline some characteristics of the public letter with regard to the traditional distinction between public speech and private conversation. The new opportunities marked by the printing press also raised new potentials for writing and publishing letters in terms of a libertas epistolaris. From a systematic point of view, public letter-writing relates to other genres, media and practices. This article therefore aims to distinguish several categories, i. e. rhetoricity and literariness, authenticity and fictionality, exclusiveness and popularity, materiality and mediality. Lastly, the special focus on the public dimensions of letter-writing might help to reconsider general assumptions about its subjectivity and spontaneity since the middle of the eighteenth century.
Gesehen am 01.09.2022